An Improved Approach for Quality of Service in Vehicular Ad Hoc Network (VANET) Using Secure-AODV (SAODV) Protocol - Devi , A.; Dhivina , K.; Eswaran , V. (International Journal of Membrane Science and Technology, 2023)
Vehicular Ad-hoc NETworks (VANETs) is a modern technology which help a vehicle and a driver in several ways. The main characteristics of VANETs are nodes i.e. vehicles with relatively high mobility and constantly changing topology. In case of data communication in VANETs, a source node must depend on the intermediate nodes to send its data packets to the destination node on multi-hop routes. VANETs can give better performance if all its nodes work properly with full cooperation during the communication. In VANETs, a node can generate and broadcast important and essential messages to other nodes in the network for safety reason. However, the generated message by a vehicle may not be reliable every time. In this situation, we have proposed a trusted and secured routing technique that evaluates the trust of a vehicle and also checks the message reliability. The proposed protocol is named as Secure Ad-hoc On Demand Distance Vector (SAODV) routing protocol which is the modification of Ad-hoc On-demand Distance Vector routing protocol. Since VANETs are mostly attacked by the malicious nodes; therefore better security solution is needed to stop such attacks. The proposed work introduces a trust model to establish a malicious node free route for source node to send its data packets to the destination node on multi-hop routes. In VANETs, a malicious node can broadcast false messages and can divert other vehicles in wrong direction. Therefore, to stop such activities an effective trust management scheme is required for VANETs. The proposed work, addressed the above mentioned problem of selection of reliable or trusty vehicles i.e. to establish a malicious node free route by proposing a trust based model for VANETs. The proposed approach evaluated the reliability and trustworthiness of the message or the vehicle based on the trust metrics of that message or the vehicle.